Determinants of Self-Assessment System Implementation: The Role of Tax Digitalization and Education Among Taxpayers in Kotawaringin Timur - Revita Dwi Handayani (Universitas Darwan Ali, 2025)
The increasing trend of national tax revenue has not been accompanied by an optimal level of taxpayer reporting compliance, particularly within the implementation of the self-assessment system. Strengthening the effectiveness of this system is therefore essential to improve taxpayer compliance. This study aims to examine the influence of tax digitalization and education level on the implementation of the self-assessment system among taxpayers in Kotawaringin Timur Regency. A quantitative research approach was employed using primary data collected through questionnaires distributed to 97 taxpayers selected through purposive sampling. The data were analyzed using logistic regression with the assistance of EViews 9 software. The empirical results indicate that tax digitalization does not have a significant effect on the implementation of the self-assessment system. In contrast, education level shows a positive and significant effect on the implementation of the self-assessment system, indicating that taxpayers with higher educational backgrounds tend to have a greater likelihood of properly implementing the system. These findings highlight that improving taxpayers’ educational capacity plays a more crucial role in supporting the effectiveness of the self-assessment system than relying solely on tax digitalization initiatives.